Propriedades mecânicas de concretos com diferentes cimentos Portland e com cinza de casca de arroz natural e moída - Trindade, Fábio Maciel de Oliveira da (2012)
Due to high rates of emissions of carbon dioxide released in cement production, an alternative to minimize this pollution is the use of rice husk ash in concrete as partial cement replacement. This research aims to investigate the technical feasibility, and the mechanical properties of the use of rice husk ash in concrete for structural purposes. Rice husk ash content to 15% by mass replacement of cement CPII-Z and CPIV were used in natural state and ground in a ball mill and compared with the reference concrete, with three water/binder relationships: 0.45; 0.55 and 0.65. Mechanical strength tests by axial compression and diametral compression at ages 28 and 91 days and elasticity modulus at 28 days were performed. The 28 days results indicated axial compression strength, modulus of elasticity and diametrical compression strength below the reference at 91 days and the concrete results with mineral admixtures were similar to the reference concrete. The mixtures containing CPII-Z, presented higher axial compressive strength than CPIV, because the higher cement consumption compared with the CPII-Z with the same w/b relationship. This fact coupled with the presence of high levels of fly ash, classifies cement CPIV with resistance to higher environmental aggressiveness, which represents more durability and useful life. It was found that mixtures containing CCAN reduced axial compressive and diametral strength compared with CCAM, because of the smaller chemical reactivity and bigger particles of CCAN compared with ground rice husk ash. These differences between the mixtures were not relevant, being about 10% and consumption of about 20 kg/m³ in relation to the same w/b compared with mixtures of CCAM for the two cement types. In conclusion, the results of the tests show that there is technical feasibility for the use of natural rice husk ash in structural concrete due to the differences observed with the ground mixtures were negligible. The values obtained in the tests were satisfactory for natural rice husk ash and ground rice husk ash with sligth advantage for the latter compared to first one, because both developed axial compressive and diametral strength and elasticity modulus similar to the reference concretes. These results reveal the greater sustainability to the concrete utilizing agriculture by-products, contributing to reducing the pollutants emissions and the global warming, due to decreased use of clinker in the mixtures.